2000
DOI: 10.1053/jhep.2000.7985
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus core protein induces apoptosis and impairs cell-cycle regulation in stably transformed chinese hamster ovary cells

Abstract: Hepatitis C virus (HCV) infection is associated with the development of hepatocellular carcinoma. Several lines of evidence suggest that the core protein of HCV may play a role in the development of this cancer. The authors examined regulation of the cell cycle in stable cell lines derived from Chinese hamster ovary (CHO-K1) cells that constitutively expressed one or more of the structural proteins of HCV. In media containing low concentrations of serum (serum starvation), cell lines expressing the core protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
77
2
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 33 publications
8
77
2
3
Order By: Relevance
“…HCV core has been described as being associated with lymphotoxin-b receptor, TNF-receptor 1, apolipoprotein AII, hnRNP and a bZIP transcription factor (Barba et al, 1997;Chen et al, 1997;Hsieh et al, 1998;Sabile et al, 1999). Evidence exists that HCV core may have an e ect upon cell transformation (Jin et al, 2000) and apoptosis (Marusawa et al, 1999;Ray et al, 1996Ray et al, , 1998Ruggieri et al, 1997); however, the biological consequences of core ectopic expression depend on the levels of expression achieved, the cell type utilized and the cellular environment (Honda et al, 2000;Zhu et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…HCV core has been described as being associated with lymphotoxin-b receptor, TNF-receptor 1, apolipoprotein AII, hnRNP and a bZIP transcription factor (Barba et al, 1997;Chen et al, 1997;Hsieh et al, 1998;Sabile et al, 1999). Evidence exists that HCV core may have an e ect upon cell transformation (Jin et al, 2000) and apoptosis (Marusawa et al, 1999;Ray et al, 1996Ray et al, , 1998Ruggieri et al, 1997); however, the biological consequences of core ectopic expression depend on the levels of expression achieved, the cell type utilized and the cellular environment (Honda et al, 2000;Zhu et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In different experimental conditions, the HCV core protein has been reported either to sensitize cells to death receptor-mediated apoptosis or to exert inhibitory effects through the activation of nuclear factor (NF)-B and induction of antiapoptotic gene products, including Bcl-2 and Bcl-x L . [15][16][17][18] It has not been determined whether steatosis or host factors such as BMI influence the apoptotic process in chronic hepatitis C. Interestingly, hepatocyte apoptosis recently was shown to be a prominent feature of nonalcoholic fatty liver disease. 19 In that study, a positive correlation was observed between hepatocyte apoptosis and both hepatic inflammatory activity and fibrosis, implicating a role for the apoptotic process in the progression of fatty liver disease.…”
mentioning
confidence: 99%
“…It has been reported that the HCV core binds to both p53 and p21 CIP1 (21,22) and impairs the cell cycle regulation in association with the increased expression of p21 CIP1 (22,35). As for the p53 status in the CL2 cells used for this study, it has been shown that the CL2 cells possess the wild-type sequence of p53 gene and do not lose its expression (50).…”
Section: Discussionmentioning
confidence: 87%
“…Thus far, the effects of HCV core on the cell cycle profile and cell cycle-related molecules have been studied by a few investigators (21,22,35). It has been reported that the HCV core can * The costs of publication of this article were defrayed in part by the payment of page charges.…”
mentioning
confidence: 99%
See 1 more Smart Citation